(3NGOe GdQhVI hGdQGaYis - (3HOQ GdOjf eMeO Hf HgGOQ Hf YHO Gddg GdRQcTis; (3GdRQcTj , eMeO Hf HgGOQ Hf YHO Gddg, HOQ GdOjf CHh YHO Gddg,J (B794 (3g` s
(3ChdgG (B:s
(3CKfGA GdcdGe Ydi HGH GdbUQ hGdaVI Hbhdg (B: (3hMce GdRcGI eHfi Ydi GdhLgjf s
(3BNQgG (B:s
(3HGH RcGI GdPgH hGdaVI s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs